Anterior Cruciate Ligament Ruptured Concomitant Meniscus Discoid in Young Patient: A Rare Case Report - I Gusti Ngurah Wien Aryana; I Ketut Wahyu Trisaputra; Febyan Febyan (Indonesian Journal of Medicine, 2023)
Background:  Abnormalities of the human meniscus, including discoid meniscus, double-layered meniscus, and ring-shaped meniscus, have been reported. The prevalence of discoid meniscus is extremely rare, with an incidence of 0.9%－2.4% in the Asian population. Traditionally, discoid meniscus concomitant anterior cruciate ligament (ACL) ruptures are extremely rare cases. The aim of this study is to discuss a rare case to provide diagnosis and management properly by using arthroscopy.Case Presentation:  A 21-year-old male Balinese, complained of pain in his right knee after fast walking for two months and an unstable knee in the past 1 year ago. On physical examination, the range of motion was limited due to the pain for flexion of more than 90°. Special tests such as Lachman test positive, and Anterior drawer test positive. The patient had medial joint line tenderness, and a McMurray test elicited pain on the medial joint line. Meanwhile, an MRI examination of the right knee showed a discoid medial meniscus with a horizontal cleavage tear and a discoid lateral meniscus with an incomplete tear. We performed a partial meniscectomy of the incomplete discoid medial meniscus and resection of the pathologic medial patellar plica. We performed surgical reconstruction of the ACL ruptured after the meniscus was repaired.Results:  We presented a 21-year-old male with discoid meniscus concomitant ACL rupture to his right knee. After the patient was performed with partial meniscectomy of the incomplete discoid medial meniscus and resection of pathologic medial patellar plica following surgical reconstruction of the ACL ruptured. The patient had no limitation of motion or pain 1 year after the operation and he had no complaints and was satisfied with the result by radiograph.Conclusion:  We concluded that This rare case of medial discoid meniscus concomitant with the ACL rupture must be reconstructed. The treatment of discoid meniscus should consider its tear pattern and whether it is symptomatic. With the development of arthroscopic techniques, the treatment of discoid meniscus has gradually changed from total meniscectomy or partial meniscectomy.Keywords:  anterior cruciate ligament, meniscus, discoid, knee, arthroscopy.Correspondence:  I Gusti Ngurah Wien Aryana. Department of Orthopaedic & Traumatology, General Central Hospital of I.G.N.G Ngoerah Central Hospital/ Faculty of Medicine, Udayana University, Bali, Indonesia. Email: wienaryanaortho@gmail.com. Mobile: +62811-385-263.Indonesian Journal of Medicine (2023), 08(03): 317-324https://doi.org/10.26911/theijmed.2023.08.03.09